Studi Replating Area Forepeak & Deep Tank pada Kapal Tanker 105 Meter Berdasarkan Hasil Pengujian Ultrasonic Thickness Test - Arif Hidayatullah; Mufti Fathonah Muvariz; Hendra Saputra; Wowo Rossbandrio; Nidia Yuniarsih (Jurnal Teknologi dan Riset Terapan (JATRA), 2023)
In shipbuilding, various stages of surveys are conducted when a vessel is declared fit for operation, encompassing annual surveys, intermediate surveys, and special/extension surveys. During these surveys, commonly encountered issues include corrosion and reduction in plate thickness associated with the ship's age and year of construction. In cases of significant thickness reduction, replating procedures are implemented. The examination of plate thickness involves ultrasonic testing utilizing the Cygnus Ultrasonic Gauge, with prior visual inspections performed on each plate section. When inspections reveal considerable thickness reduction and indications of corrosion during visual tests, such instances are evident in areas like the forepeak and deep tank. Substantial thickness reduction is noted on both the port and starboard sides, covering a dimension of 1,200 mm Ã— 400 mm along each plate line, employing standard 12 mm thickness material. Test results are obtained for plate lines numbered 1 to 4 on the port and starboard sides of the Forepeak Tank area, as well as plate lines numbered 1 to 3 on the port side and plate lines numbered 1 to 4 on the starboard side within the Deep Tank region.